Migratory outflow from Wrocław: Directions of population flows within the frame- work of internal migration in the period 2002–2018 - Długosz, Mateusz; Szmytkie, Robert (Quaestiones Geographicae, 2021)
In the majority of large cities in Poland there is a migration outflow, resulting mainly from suburbanisation processes. However, it should be noted that the inhabitants of large cities do not move exclusively to the suburban zone. The study below focuses on the migratory outflow of Wrocław residents. The authors characterise it by presenting the directions of population movements and determining their sustainability. The authors conclude that the target area of immigrants from Wrocław is mostly a suburban area, but there are also permanent migration flows to other rural communities in the voivodeship and other large cities in the country. The area of emigration itself goes beyond the scope of the voivodeship of which Wrocław is the capital.